2020
DOI: 10.2147/jpr.s204788
|View full text |Cite
|
Sign up to set email alerts
|

<p>MRI Changes After Platelet Rich Plasma Injection in Knee Osteoarthritis (Randomized Clinical Trial)</p>

Abstract: Purpose: Few papers have studied the objective effects of PRP on cartilage. In this study, we investigated the effect of PRP on cartilage characteristics by special MRI sequencing in knee osteoarthritis (IRCT registration number: 2014020413442N6). Patients and methods: In this double blind randomized clinical trial, patients with bilateral knees osteoarthritis-grade 1, 2, and 3 were included in the study. Each patient's knees were randomly allocated to either control or treatment groups. PRP was injected in tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 35 publications
2
47
0
Order By: Relevance
“…Moreover, over the time the exogenous HA is destroyed in the inflammatory site and thus the symptoms start again after a period post-injection. In the case of the PRP or PRGF, it has been shown that these products could stimulate chondrogenesis, modulate the intra-articular microenvironment as well as cellular composition and proliferation, and directly affect the expression of some major inflammatory mediators in the joint, thus their effect may remain for a longer time compared to the ozone or HA [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, over the time the exogenous HA is destroyed in the inflammatory site and thus the symptoms start again after a period post-injection. In the case of the PRP or PRGF, it has been shown that these products could stimulate chondrogenesis, modulate the intra-articular microenvironment as well as cellular composition and proliferation, and directly affect the expression of some major inflammatory mediators in the joint, thus their effect may remain for a longer time compared to the ozone or HA [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The flexion range of motion became better with the increase in the total number of visits among grade IV knees, and we observed an overall improvement in flexion in grade IV more than grade II knees. Radiological imaging showed an improvement in our patients in comparison to the patients included in the Raeissadat et al study (Figure 6 ) [ 30 ].…”
Section: Discussionmentioning
confidence: 46%
“…The flexion range of motion became better with the increase in the total number of visits among grade IV knees, and we observed an overall improvement in flexion in grade IV more than grade II knees. Radiological imaging showed an improvement in our patients in comparison to the patients included in the Raeissadat et al study ( Figure 6) [30]. Despite the positive outcomes that are reported in the literature, the diversity of the methodological studies that include preparation, administration and intervals of the injection.…”
Section: Discussionmentioning
confidence: 46%
“…In summary, although there are still many controversies, some clinical trials have also confirmed the application value of PRP in promoting repair, relieving pain and providing some functional benefits, such as osteoarthritis [ 81 , 82 ], synovitis [ 83 ], and refractory wounds [ 84 , 85 ]. In the future, PRP may be a potential auxiliary therapy for military drill injury.…”
Section: Resultsmentioning
confidence: 99%